Features of the promotion policy of the confectionery industry (Economics and region, 2019)
The article defines the essence and purpose of the product promotion process on the market, the specified stages of its promotion. The organization features of this process taking into account product specifics are considered. The algorithm of technologies improvement, organization of production processes and management of the enterprise during the innovative products promotion on the market is offered. New forms of stimulation, organizational structures and methods for developing managerial decisions are all innovative products. In order to accelerate and improve the quality of the product promotion process on the market, business entities are encouraged to share their knowledge of potential customers with partners.The modern tendency of organizing the product promotion process on the market is the search for enterprises of vertical and horizontal international links with each other due to the shortage of own funds, rising cost of borrowed resources, the complication of attracting investments, reducing the life cycle of innovative products, the need for the integrated use of various methods of promotion and other factors. In addition, the attention was paid to the study of the promotion policy specifics in the confectionery industry. The theoretical, methodological principles of formation and implementation of the promotion policy at the confectionery industry enterprises are considered. The factors that need to be taken into account while developing new markets are described in the article. The main directions of the confectionery industry enterprises, as well as the competitive advantages that the enterprise receives through promotion policy, are considered.The promotion policy is more detailed analyzed on the example of the confectionery firm "Dominic". Based on the made analysis, the assumption was made that in the confectionery industry it is expedient to introduce the latest modern methods of product promotion in order to obtain the leading enterprises. Further perspectives of the industry, taking into account the establishment of functional confectionery products production, are considered.
Keywords: market; products; confectionery; enterprise; technology